Construire des connaissances sur les pratiques d’enseignement : travail d’objectivation et vigilance épistémologique - Gwénaël Lefeuvre (Éducation et Socialisation)
Based on the thinking of Pierre Bourdieu on the objectification of objectifying position, we will examine in this article the unthought and assumptions that were ours in conducting a research on teaching practices. After recalling the positioning of Bourdieu reflective analysis practical knowledge, we will present the protocol of a research conducted in one year with a teacher preparation course in order to analyze their teaching practices. We will question the assumptions of the theoretical framework of choice - in this case the “conceptualization in action“ developed by Vergnaud - then those concerning the selection of a particular methodological device maintenance in a situation of self-confrontation. To participate in the opening of discussions on current sociological conditions of the scientific study of educational science education practices this test of self-analysis aims.